KEDUDUKAN FATWA TERHADAP DASAR HUKUM PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BASYARNAS - Nunung Rodliyah; Nila Nargis; Abdur Rohman Husen (Nizham Jurnal Studi Keislaman, 2019)
The role of fatwa in supporting the implementation and implementation of sharia law in Indonesia is very diverse, for example in the implementation of contract agreements. Ideal contract in the contract of national sharia In language, the word "contract" comes from the Arabic language al-qAqd which is used in many meanings, all of which return to the meaning of the bond or merging two things. This definition includes all types of commitments, both from two or more parties, such as buying and selling contract, rent and marriage contract and others. The problems discussed in this paper are the Legal Basis of the Strength of Binding Fatwa in Regulating the Settlement of Sharia Economic Disputes in Indonesia through Basyarnas.The results discussed regarding Fatwa are solutions that provide religious answers to the problems that arise which are always developing and so complex, besides discussing the mechanism of proceedings in Basyarnas.Conclusion of this writing, Fatwa is increasingly developing as the times develop and its role in supporting the construction of the legal basis must be strengthened or at least be a special consideration for judges to resolve disputes on a concrete basis and can be accepted logically by litigants.